Analysis of validity and reliability of a questionnaire to assess conceptual knowledge about inclined plane and acceleration - Rafaela Dinali Nascimento; Alessandro Damásio Trani Gomes (Amazônia, 2017)
This paper discusses the importance of establishing the validity and reliability of data collection instruments in the research in science teaching. We present the process of analysis of a mixed questionnaire about accelerated movement and inclined plane, applied to 185 high school students of a federal public school. This eight questions questionnaire passed through the processes of content and predictive validations. Cronbach's alpha and Silveira´s beta coefficients were calculated to determine the internal consistency of the questionnaire. By this process, the adequacy of the questionnaire to evaluate the conceptual knowledge of students on acceleration and an inclined plane was verified. Based on the literature review, some implications were made for the research area and for science teaching.